Molecular interactions, proton exchange, and photoinduced processes prompted by an inclusion process and a [2]pseudorotaxane formation - Mandal, Amal Kumar; Suresh, Moorthy; Kesharwani, Manoj K.; Gangopadhyay, Monalisa; Agrawal, Manoj; Boricha, Vinod P.; Ganguly, Bishwajit; Das, Amitava (Journal of Organic Chemistry, 2013)
Appropriate design of the host and guest components allows formation of a novel [2]pseudorotaxane complex with an interrupted photoinduced electron transfer (PET)-coupled fluorescence resonance energy transfer (FRET) response. This is the first example of an inclusion complex with NO6-based azacrown ether as the host unit (H). Different guest molecules (G1, G2, G3, and G4) with varying stopper size are used for the studies. Unlike G1, G2, and G3, G4 with a relatively bulkier stopper fails to form a [2]pseudorotaxane complex. Isothermal titration microcaloiimetry measurements reveal a systematic increase in the association constant for H.G1, H.G2, and H.G3 with a change in the stopper size. Thermodynamic data suggest that the formation of H.G1/H.G2/H.G3 is exclusively driven by a large positive entropic gain (T Delta S = 19.69/26.80/21.81 kJ.mol(-1)), while the enthalpy change is slightly negative for H.G1/H.G3 (-2.61/-1.97 kJ.mol(-1)) and slightly positive for H.G2 (Delta H = 5.98 kJ.mol(-1)). For these three inclusion complexes, an interrupted PET-coupled FRET response is observed with varying efficiency, which is attributed to the subtle differences in acidity of the NH2+ unit of the guest molecules and thus the proton exchange ability between the host and respective guest. This is substantiated by the results of the computational studies.

Fluorescent probes for the detection of cyanide ions in aqueous medium: cellular uptake and assay for beta-glucosidase and hydroxynitrile lyase - Agarwalla, Hridesh; Gangopadhyay, Monalisa; Sharma, Dharmendar Kumar; Basu, Santanu Kumar; Jadhav, Sameer; Chowdhury, Arindam; Das, Amitava (Journal of Materials Chemistry B, 2015)
A chemodosimteric reagent (1) for the efficient detection of cyanide species (CN- and/or HCN) in aq. medium as well as under physiological conditions has been described. Selective reaction of the cyanide species with this reagent in the presence of all common interfering anions, amino acids and glutathione (GSH) led to the generation of the corresponding cyanohydrin derivative. The formation of the cyanohydrin derivative of the probe is associated with a visually detectable change in solution fluorescence in aq. buffer medium with 1.9 mu M NaCN, the threshold limit set by WHO for the safe drinking water and this makes this fluorogenic sensor an ideal candidate for in-field applications. An apparent switch on the luminescence response, ultralow detection limit, low response time, cell membrane permeability and insignificant toxicity are key features of a probe molecule, which gives it a distinct edge over previously reported chemodosimetric reagents for the detection of cyanide species (CN- or HCN) in an aqueous environment. This methodology could be used for developing a generalized and efficient fluorescence-based assay for crucial enzymes like beta-glucosidase and hydroxynitrile lyase. Furthermore, spectrally-resolved fluorescence microscopy measurements on single-cells revealed that this sensor molecule could also be used for imaging the cellular uptake of cyanide species from aq. solution contaminated with NaCN. Our results confirmed that statistical analysis of integrated intensity and transition energy obtained from the emission spectra collected over various microscopic sub-cellular regions can potentially be used to discriminate the effects of local cellular environments and that due to cyanide detection.

Photo-responsive pseudorotaxanes and assemblies - Mandal, Amal Kumar; Gangopadhyay, Monalisa; Das, Amitava (Chemical Society Reviews, 2015)
Chemists have achieved a predictable control over various non-covalent interactions and have used these weak interactions in their favour for developing a plethora of intricate functional structures. In this tutorial review we have summarized reports on such supramolecular structures that describe the rational approach in designing host and/or guest components, tagged with an appropriate fluorophore, for achieving the modified optical responses on formation of an assembly. This has relevance for designing new photo-responsive smart or adaptive stimuli responsive functional materials, self- healable materials, with interesting photo-physical property. These are also important in the area of supramolecular chemistry and biophysical chemistry in predicting the relative conformation in solution.

[2]Pseudorotaxane formation with fret based luminescence response: demonstration ofboolean operations through self sorting on solid surface - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Das, Amitava (Journal of Organic Chemistry, 2016)
Binary pseudorotaxane formation between an aza crown derivative as host (H) and two different imidazolium derivatives as guests (G(1) and G(2)) have been studied in detail by NMR (H-1 NMR, 2D NOESY), optical (steady state electronic and emission spectroscopy), and mass spectroscopy. Binding stoichiometry (1:1), association constant for the respective [2]pseudorotaxane formation (K-a(H center dot G1) = (2.61 +/- 0.015) X 10(3) M-1 and K-a(H center dot G2) = (1.27 +/- 0.16) X 10(3) M-1), and associated thermodynamic parameters are also evaluated based on isothermal titration calorimetric (ITC) studies. FRET based luminescence ON responses are observed on formation of the binary pseudorotaxane (H center dot G(1) and H center dot G(2)) in a nonpolar medium like dichlororriethane. The thermodynamic feasibility of such an energy transfer process is also examined. The higher affinity of H and 18-crown-6 toward K+, as compared to those toward G(1) or G(2), and the reversibility in the host- guest binding process are utilized in demonstrating the self-sorting phenomena with associated changes in luminescence responses that could be correlated for Boolean operators like YES, INHIBIT, OR, and AND gates.

Counteranion driven homochiral assembly of a cationic C-3-symmetric gelator through ion-pair assisted hydrogen bond - Maity, Arunava; Gangopadhyay, Monalisa; Basu, Arghya; Aute, Sunil; Babu, Sukumaran Santhosh; Das, Amitava (Journal of the American Chemical Society, 2016)
The helical handedness in achiral self-assemblies is mostly complex due to spontaneous symmetry breaking or kinetically controlled random assembly formation. Here an attempt has been made to address this issue through chiral anion exchange. A new class of cationic achiral C-3-symmetric gelator devoid of any conventional gelation assisting functional units is found to form both right-and left-handed helical structures. A chiral counteranion exchange-assisted approach is successfully introduced to control the chirality sign and thereby to obtain preferred homochiral assemblies. Formation of anion-assisted chiral assembly was confirmed by circular dichroism (CD) spectroscopy, microscopic images, and crystal structure. The X-ray crystal structure reveals the construction of helical assemblies with opposite handedness for (+)- and (-)-chiral anion reformed gelators. The appropriate counteranion driven ion-pair-assisted hydrogen-bonding interactions are found responsible for the helical bias control in this C-3-symmetric gelator.

Tuning emission responses of a triphenylamine derivative in host-guest complexes and an unusual dynamic inclusion phenomenon - Gangopadhyay, Monalisa; Mandal, Amal K.; Maity, Arunava; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Journal of Organic Chemistry, 2016)
A newly synthesized triphenylamine derivative (1Cl(3)) shows significant differences in inclusion complex formation with two different macrocyclic hosts, cucurbit[7]uril (CB[7]) and beta-cyclodextrin (beta-CD). Detailed investigations by NMR spectroscopy reveal that CB[7] forms a 1:3 host-guest complex ([1 center dot 3{CB[7]}]Cl-3) in which three arms of 1Cl(3) are bound to three host molecules. On the other hand, beta-CD forms a dynamic 1:1 inclusion complex ([1 center dotbeta-CD]Cl-3) by binding to only one of the three arms of 1Cl(3) at a given time. The formation of a 1:1 host-guest complex with beta-CD and 1:3 host-guest complex with CB[7] was also confirmed from the results of the isothermal titration calorimetric studies. Interestingly, 1Cl(3) exhibits a rare dual emission property in solution at room temperature with the lower and higher energy bands arising from a locally excited state and an intramolecular charge-transfer transition, respectively. The difference in inclusion complex formation behavior of 1Cl(3) with the two macrocyclic hosts results in the stabilization of different emission states in the two inclusion complexes. The fundamental difference in the electrostatic surface potentials, cavity polarities, and shapes of the two macrocyclic hosts could account for the formation of the different inclusion complexes with distinct luminescence responses.

Chiral discrimination through h-1 nmr and luminescence spectroscopy: dynamic processes and solid strip for chiral recognition - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Rajamohanan, P. R.; Ravindranathan, Sapna; Das, Amitava (Chemistry-A European Journal, 2017)
The appropriate choice of the host molecules with well-defined optical activity (S-H/R-H) helps in the differentiation between two secondary ammonium ion-derivative guest molecules with different optical activities (R-G/S-G) based on the fluorescence resonance energy transfer (FRET)based luminescence responses. Crown ether-based host molecules with opposite chiral configurations (R-H, S-H) have been derived from 1,1'-bi-2-naphthol (BINOL) derivatives that have axially chiral biaryl centers. These chiral crown ethers form host-guest complexes (i.e., [2] pseudoro-taxanes) with chiral secondary ammonium ion derivatives (R-G, S-G). NMR spectroscopic studies show that the complexes are in a dynamic equilibrium in solution. Results of the H-1 NMR and fluorescence spectroscopic studies indicate a head-on orientation of the host and guest in the [2] pseudorotaxanes. The difference in the efficiency in the FRET-based responses between anthracene and the BINOL derivatives allow efficient chiral discrimination of the guests. Isothermal titration calorimetry and NMR investigations reveal that inclusion complexes between hosts and guests of the same chirality (R-H center dot R-G, S-H center dot S-G) are more stable relative to those of opposite chirality (R-H center dot S-G, S-H center dot R-G). However, FRET-based energy-transfer efficiency is higher for R-H center dot S-G and S-H center dot R-G complexes. NMR spectroscopic studies show that the relative orientation of the guest in the host cavity is significantly different when the host binds a guest of the same or opposite chirality; furthermore, the latter is more favorable for FRET, thus enabling discrimination between enantiomers. Interestingly, chiral discrimination of guest ions could also be achieved by using silica surfaces modified with chiral host molecules.

Cucurbit[7]uril induced formation of fret-enabled unilamellar lipid vesicles - Kushwaha, Shilpi; Maity, Arunava; Gangopadhyay, Monalisa; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Langmuir, 2017)
A unique fluorescence resonance energy transfer (FRET) process is found to be operational in a unilamellar lipid self-assembly in the aqueous phase. A newly synthesized naphthyl based long chain lipid derivative [N-(naphthalene-1-ylmethyl)tetradecane-1-ammonium chloride, 14NA(+)] forms various self-assembled architectures in the aqueous phase. Controlled changes in lipid concentration lead to a transition of the self-assemblies from micelles to vesicles to rods. In the presence of cucurbit[7]uril (CB7), 14NA(+) forms a host-guest [2]pseudorotaxane complex (CB7(sic)14NA(+)) and secondary interactions lead to the formation of a lipid bilayer with hydrophobic pockets situated in between the layers. The change in the structure of 14NA(+) assemblies, interaction with CB7 and formation of supramolecular assemblies of CB7(sic)14NA(+) were examined using light scattering, spectroscopic, and microscopic techniques. Entrapment of a luminescent dye, anthracene within the hydrophobic bilayer of the supramolecular assembly CB7(sic)14NA(+) favors a modified luminescent response due to an efficient FRET process. Further, the FRET process could be controlled by thermal and chemical stimuli that induce transformation of unilamellar vesicles.

Water induced morphological transformation of a poly(aryl ether) dendron amphiphile: helical fibers to nanorods, as light-harvesting antenna systems - Maity, Arunava; Dey, Ananta; Gangopadhyay, Monalisa; Das, Amitava (Nanoscale, 2018)
Self-assembly of suitable molecular building blocks is an efficient and convenient approach to generate nanomaterials with various morphologies and functions. Moreover, understanding the nature of molecules and controlling factors of their self-assembly process is crucial in fundamental aspects of molecular self-assembly which provide insights into the design of new assemblies with functional nano-architectures. To this end, the present study reports water induced self-assembled multifaceted morphology formation and the plausible pathway of the morphology transformation of a single poly(aryl ether) dendron amphiphile 1(D). In THF, 1(D) self-assembles into helical fibers. However, with an increase in the water fraction in its THF solution, the morphology changes to nanorods through an intermediate scroll-up pathway of exfoliated fibers. The nanorod formation and transformation of 1(D) are investigated using various microscopy and spectroscopy techniques, which indicate that it has highly ordered multilayered arrays of 1(D) molecules. Finally, these multilayered arrays of 1(D) nanorods are exploited for constructing a model light-harvesting system via the incorporation of small quantities of two newly designed BODIPY based molecules as energy acceptors and 1(D) as an antenna chromophore.